2014
DOI: 10.12816/0008205
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Region : A Reservoir for CTX - M - ESBL - Producing Enterobacteriacae

Abstract: The incidence of ESBL-producing bacteria is increasing worldwide, which represents a challenge for the healthcare systems. More recently, the emergence of the CTX-M group has been frequently reported as being associated with both nosocomial and community acquired infections. CTX-M-15 was identified as being the most prevalent in a large geographic area including Europe and the Middle East, suggesting the presence of a community reservoir of CTX-M enzymes disseminating in the Mediterranean area. Thus, this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…In the present study, the overall prevalence rate of ESBL-producing E. coli isolates was 39.1%. Similar studies have shown 16.8% in Lebanon [14], 22.9% in Jordan [15], 42.3% in Egypt [16], and 52% in Syria [17]. We observed that 59.3% (n=16) of the K. pneumoniae isolates were ESBL producers in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the overall prevalence rate of ESBL-producing E. coli isolates was 39.1%. Similar studies have shown 16.8% in Lebanon [14], 22.9% in Jordan [15], 42.3% in Egypt [16], and 52% in Syria [17]. We observed that 59.3% (n=16) of the K. pneumoniae isolates were ESBL producers in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…In many parts of the middle east, the prevalence of ESBL-producing K. pneumoniae isolates has been reported, e.g., United Arab Emirates (36%) [11], Syria (67.5%) [12], and Jordan (70%) [13]. Data from some countries showed that the prevalence of ESBL-producing E. coli was 16.8% in Lebanon [14], 22.9% in Jordan [15], 42.3% in Egypt [16], and 52% in Syria [17].…”
Section: Introductionmentioning
confidence: 99%
“…20 Nonetheless, numerous reports are available from Middle East and North African countries. 9,10 In this report, 14 of the16 K. pneumoniae clinical isolates harbored ESBLs of the CTX-M-1 group, including isolates encoding bla CTX-M-15 (n = 13) and bla CTX-M-3 (n = 1) genes. This finding is in agreement with recent reports both in Middle East and other parts of the world, where CTX-M-15 remains the globally predominant ESBL enzyme.…”
Section: Discussionmentioning
confidence: 76%
“…8 In the Middle East, several reports highlighted to what extent the spread of ESBL producers has become of serious concern, and this region might indeed be one of the major epicenters of the global ESBL pandemic. 9,10 The clonal dissemination of CTX-M-15-producing K. pneumoniae isolates has been reported in Saudi Arabia, Egypt, Iran, Oman, Lebanon, Gulf Council, Iraq, Kuwait, and Turkey. 9,[11][12][13][14][15][16][17][18][19] No data are available, so far, on ESBL-producing K. pneumoniae in Gaza Strip, Palestine and very scarce data in West Bank, Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…The above frequencies varies with geographical areas of the performed studies, however, the global trends indicated an increase of CTX-M gene in ESBL E. coli isolates and became responsible for outbreak of community and hospital acquired UTI infection [15,22,[38][39][40][41][42][43]. The higher frequency rate of E. coli antibiotic resistance gene was demonstrated by bla -OXA gene (100%; 15/15), followed by bla CTX-M gene (86.7%, 13/15), and bla-TEM gene (66.7%, 10/15), while the lowest one was bla SHV gene which was detected in 60% (9/15) of the isolates.…”
Section: Figure (4) Molecular Detection Of Bla Shv Antibiotic Resistmentioning
confidence: 99%